การนำเสนอรายวิชาฝึกอบรมภาษาอังกฤษเพื่อวัตถุประสงค์เฉพาะสำหรับพนักงานสอบสวน A PROPOSED ESP TRAINING COURSE FOR INVESTIGATION OFFICERS - ไชยวงษ์ ประภาพิศ; มีศรี ราเชน (An Online Journal of Education, 2014)
การวิจัยนี้นำเสนอกระบวนการในการพัฒนาหลักสูตรการฝึกอบรมภาษาอังกฤษเพื่อพนักงานสอบสวนมีจุดประสงค์เพื่อ 1) วิเคราะห์ความต้องการของผู้มีส่วนได้ส่วนเสียและพนักงานสอบสวนเพื่อการออกแบบประมวลรายวิชาในการจัดอบรม 2) เสนอประมวลรายวิชาในการฝึกอบรมภาษาอังกฤษสำหรับพนักงานสอบสวน การวิจัยครั้งนี้เก็บข้อมูลทั้งเชิงปริมาณและคุณภาพ มีผู้เข้าร่วมทั้งหมด 48 คน ดังนี้ 1) ครูชาวต่างชาติที่สอนภาษาอังกฤษสำหรับตำรวจ 3 คน 2) ผู้บังคับบัญชาระดับชั้นนายพัน2 คน 3) ตำรวจที่เคยอบรมหลักสูตรภาษาอังกฤษสำหรับตำรวจ 3 คน 4) พนักงานสอบสวนจำนวน 40 คน เครื่องมือที่ใช้ในการวิจัยครั้งนี้มี 2 ประเภทคือแบบสัมภาษณ์และแบบสอบถาม ผลการวิจัยแบ่งตามกรอบแนวคิดการวิเคราะห์ข้อมูลความจำเป็นได้ ดังนี้ 1) จากการวิเคราะห์ความต้องการของผู้มีส่วนได้ส่วนเสียและพนักงานสอบสวนเพื่อออกแบบประมวลรายวิชา พบว่าควรมีหัวข้อครอบคลุมในการจัดอบรมดังนี้ คดีทรัพย์สินสูญหาย คดีลักทรัพย์ คดีอุบัติเหตุ คดีทำร้ายร่างกาย คดีหลบหนีเข้าเมือง ทักษะการพูดและการฟังเป็นทักษะที่สำคัญและเป็นทักษะที่พนักงานสอบสวนต้องการพัฒนามากที่สุด และผู้เรียนส่วนใหญ่เรียนรู้ได้ดีจากการใช้สายตา 2) ประมวลรายวิชาในการฝึกอบรมสำหรับพนักงานสอบสวน ควรจัดการอบรมในรูปแบบของการเรียนรู้ก่อนแล้วจึงสอนทฤษฏีภายหลัง กิจกรรมต่างๆจัดในรูปแบบที่เหมาะสมกับผู้เรียนที่ใช้สายตาเป็นหลัก และเนื้อหาที่ใช้จัดเป็นหัวข้อที่เกี่ยวกับสถานการณ์ที่ต้องเจอขณะปฏิบัติงาน การจัดอบรมควรครอบคลุมเนื้อหาทั้งหมด 5 หัวข้อคือ คดีลักทรัพย์ คดีหลบหนีเข้าเมือง คดีอุบัติเหตุ คดีทำร้ายร่างกาย และคดีปล้น-ชิงทรัพย์ จัดการเรียนรู้ในการอบรมโดยยึดหลักการภายใต้ situational-based learning. This paper presents an English course for investigation officers. The purposes of the study were 1) to explore the needs of the investigation officers and 2) to propose an ESP training course intended for the investigation officers. The total number of participants was 48, including 3 foreign teachers teaching an English training course to police officers, 2 commanders, 3 police officers who had taken English courses for police officers, and 40 investigation officers. The instruments to collect the data were a semi-structured interview and a questionnaire. The key findings revealed that 1) The result of the needs analysis of the stakeholders and investigation officers to propose the syllabus showed that the syllabus should cover 5 different cases: loss, robbery, accident, fight, and immigration cases, which were considered important as target learning situations for the investigation officers. They were considered visual and audio learners because the most important skills they wanted to improve were speaking and listening. 2) The course syllabus was proposed based on the learners’ needs with respect to this, the inductive method used as a teaching methodology to enhance their English proficiency, and the activities provided in a visual and audio format., the topics in the syllabus concerned with the situations that the investigation officers usually face in the workplace. The contents covered 5 topics: loss, robbery, accident, fight, and immigration cases and lastly, the learning content organized as situational-based learning.